Effect of interface-dependent crystalline boundary on sub-threshold characteristics in a solution-processed 6, 13-bis(triisopropylsilylethynyl)-pentacene thin-film transistor. Issue 3 (24th March 2014) - Kwon, Jin-Hyuk; Kang, In Man; Bae, Jin-Hyuk
Abstract : We demonstrate how the sub-threshold characteristics are affected by the density of crystalline domain boundaries directly governed by an organic semiconductor (OSC) – a gate insulator interface in a solution-processed 6, 13-bis(triisopropylsilylethynyl)-pentacene (TIPS-pentacene) thin-film transistor (TFT). For generation of an engineered interface, a self assembled monolayer of octadecyltricholorosilane (OTS) was produced between a solution processed TIPS-pentacene film and a silicon dioxide layer. The interfacial charge trap density ( N trap ) deduced from the sub-threshold characteristics was significantly minimized after OTS treatment due to reduced crystal domain boundaries in the TIPS-pentacene film. In addition, the carrier mobility exhibits a value twice as large by OTS treatment. It is found that less crystal domain boundaries in the solution-processed OSC obtained from the engineered interface play an important role in inducing improved sub-threshold characteristics together with increased carrier mobility in organic TFTs.